The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.2147/ijn.s32311
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration of gene transfection efficiency in neuroblastoma cells through polyethyleneimine/poly(methyl methacrylate) core-shell magnetic nanoparticles

Abstract: Background:The purpose of this study was to demonstrate the potential of magnetic poly(methyl methacrylate) (PMMA) core/polyethyleneimine (PEI) shell (mag-PEI) nanoparticles, which possess high saturation magnetization for gene delivery. By using mag-PEI nanoparticles as a gene carrier, this study focused on evaluation of transfection efficiency under magnetic induction. The potential role of this newly synthesized nanosphere for therapeutic delivery of the tryptophan hydroxylase-2 (TPH-2) gene was also invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Several substances such as chitosan [83], PEI (polyethyleneimine) nanoparticles [84], 15% of N-acetyl cysteine (NAC) [87], calcium phosphate cement (CPC) [90], acrylic resin of different colors [91], (bone cement) enriched with microencapsulated 2-octyl cyanoacrylate (OCA), extracts solutions [92], scaffolds fabricated by electrospinning using polycaprolactone (PCL) [94], core/polyethyleneimine (PEI) shell magnetic nanoparticles [97], silver nanoparticles (AgNPs) [98], and Paladon 65-HR precoated with biosurfactant were also evaluated for cytotoxicity. The authors observed reduction in cytotoxicity and increase in biocompatibility from non-cytotoxic (cell viability higher than 75%) to slightly cytotoxic (cell viability ranging from 50 to 75%)…”
Section: Short-or Long-term Injection or Implantation Studiesmentioning
confidence: 99%
“…Several substances such as chitosan [83], PEI (polyethyleneimine) nanoparticles [84], 15% of N-acetyl cysteine (NAC) [87], calcium phosphate cement (CPC) [90], acrylic resin of different colors [91], (bone cement) enriched with microencapsulated 2-octyl cyanoacrylate (OCA), extracts solutions [92], scaffolds fabricated by electrospinning using polycaprolactone (PCL) [94], core/polyethyleneimine (PEI) shell magnetic nanoparticles [97], silver nanoparticles (AgNPs) [98], and Paladon 65-HR precoated with biosurfactant were also evaluated for cytotoxicity. The authors observed reduction in cytotoxicity and increase in biocompatibility from non-cytotoxic (cell viability higher than 75%) to slightly cytotoxic (cell viability ranging from 50 to 75%)…”
Section: Short-or Long-term Injection or Implantation Studiesmentioning
confidence: 99%